Integration of a vector containing a repetitive LINE-1 element in the human genome. - Richard, M (1994)
Mammalian cells contain numerous nonallelic repeated sequences, such as multicopy genes, gene families, and repeated elements. One common feature of nonallelic repeated sequences is that they are homeologous (not perfectly identical). Our laboratory has been studying recombination between homeologous sequences by using LINE-1 (L1) elements as substrates. We showed previously that an exogenous L1 element could readily acquire endogenous L1 sequences by nonreciprocal homologous recombination. In the study presented here, we have investigated the propensity of exogenous L1 elements to be involved in a reciprocal process, namely, crossing-overs. This would result in the integration of the exogenous L1 element into an endogenous L1 element. Of over 400 distinct integration events analyzed, only 2% involved homologous recombination between exogenous and endogenous L1 elements. These homologous recombination events were imprecise, with the integrated vector being flanked by one homologous and one illegitimate junction. This type of structure is not consistent with classical crossing-overs that would result in two homologous junctions but rather is consistent with one-sided homologous recombination followed by illegitimate integration. Contrary to what has been found for reciprocal homologous integration, the degree of homology between the exogenous and endogenous L1 elements did not seem to play an important role in the choice of recombination partners. These results suggest that although exogenous and endogenous L1 elements are capable of homologous recombination, this seldom leads to crossing-overs. This observation could have implications for the stability of mammalian genomes.